2013
DOI: 10.1093/ndt/gft332
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and non-canonical effects of the NLRP3 inflammasome in kidney inflammation and fibrosis

Abstract: NLRP-3 inflammasome is one of several intracellular danger recognition platforms that integrates infectious or non-infectious types of danger into the expression of pro-inflammatory cytokines to set-up inflammation for danger control. NLRP3 activation induces three types of caspase-1-mediated responses: secretion of IL-1beta, secretion of IL-18 and a programmed form of cell death, referred to as pyroptosis. Similar to the well-documented impact of Toll-like receptor-driven danger signalling in kidney disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 61 publications
3
136
0
10
Order By: Relevance
“…Increasing evidence implicates the NLRP3 inflammasome and its activation products IL-1b, IL-18, IL-1a, and high-mobility group box 1 in the pathogenesis of tissue injury and disease (4,8,9,(12)(13)(14)(15)44). Therefore, a potent, selective, and orally available pharmacological inhibitor of NLRP3 inflammasome should be useful for elucidating the pathogenic contributions of NLRP3 inflammasome activation and its multiple products in preclinical disease models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence implicates the NLRP3 inflammasome and its activation products IL-1b, IL-18, IL-1a, and high-mobility group box 1 in the pathogenesis of tissue injury and disease (4,8,9,(12)(13)(14)(15)44). Therefore, a potent, selective, and orally available pharmacological inhibitor of NLRP3 inflammasome should be useful for elucidating the pathogenic contributions of NLRP3 inflammasome activation and its multiple products in preclinical disease models.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the ability of CP-456,773 to inhibit NLRP3 activation induced by crystalline activators that have been associated with inflammatory diseases (2,4,9,27). In the results shown in Fig.…”
Section: Cp-456773 Inhibits Release Of Il-1b Induced With Both Solubmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,20,[50][51][52][53] But are the inflammasome components expressed at all in the kidney and, if so, do they contribute to canonical inflammasome signaling 54,55 ? IL-1a and IL-1b are both induced by NF-ĸB signaling but still display heterogeneous expression patterns in solid organs of healthy mice.…”
Section: Data In Renal Cells: Expression Releasementioning
confidence: 99%
“…These results are consistent with other reports showing noncanonical effects of Nlrp3 in the kidney. 15,16,27,29 Next to cytokines, renal function is influenced by tubular damage and repair. Interestingly, we observed that renal apoptosis was reduced in mice lacking Nlrp3 expression in leukocytes, suggesting that leukocyte-associated Nlrp3 influences tubular epithelial apoptosis and, thereby, renal dysfunction.…”
Section: Nlrp3 Regulates Renal Repairmentioning
confidence: 99%